PERANCANGAN STRATEGI PEMASARAN IRT KERIPIK UBI CILEMBU CIHUY CHIPS MENGGUNAKAN SOAR STRATEGIC - Rizky Fitria Hartuti; Dini Rochdiani (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Sweet potatoes are one of the leading food crop commodities in Indonesia with a total production of 1,914,244 tons. Sumedang Regency is one of the sweet potato production centers in West Java with a productivity of 244.84 quintals per hectare with cilembu sweet potatoes as the main variety. The growth rate of cilembu sweet potato production and productivity shows that cilembu sweet potato has the potential to be developed by reprocessing it, one of which is into chips. One of the home industries that process cilembu sweet potato into chips product is Cihuy Chips Home Industry. This study aims to determine the marketing strategies that can be applied to Cihuy Chips Home Industry. Data collection was carried out from July to August 2020 through observations and interviews with informants using the SOAR analysis stage. The analysis tools that used are the SOAR diagram and the SOAR matrix. The marketing strategy formulated from the SOAR matrix so that the Cihuy Chips Home Industry can survive and thrive is to provide discounts on the flavor variants that are not best-sellers, procure limited edition greentea and salt chilies flavors in online store Shopee, renew the design packaging, logo and addition of zip locks, launching of cheesestick and eggroll products with free shipping fee at Shopee's online store, and buy 1 get 1 promotions on products that are nearing expiration date.